Penggunaan model pembelajaran talking stick untuk meningkatkan pemahaman konsep simbol-simbol sila pancasila pada peserta didik kelas II sekolah dasar - Paraisu, Jessica Sellyn; Mahfud, Hasan; Adi, Fadhil Purnama (Didaktika Dwija Indria, 2020)
This research aims to improve the understanding of the concepts of the Pancasila precepts by using the talking stick learning model. This research was Classroom Action Research (CAR) consisting of two cycles, each cycle consisting of two meetings with four stages there are planning,action,observation,reflecting. Data collection techniques are tests, interview, observations, and documentation. Data validity uses triangulation of methods and data sources. Data analysis techniques using interactive analysis techniques. The results of the study prove that the use of the talking stick model can increase the understanding of the concepts of the Pancasila precepts.